Epidemiology of Newcastle disease in village chickens in Ethiopia : risk factors, molecular characterization and role of poultry markets - Thompson, P.N. (Peter N.) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.